Chapter La ricerca e (è) la vita: per introdurre - Boffo, Vanna (Studies on Adult Learning and Education, 2022)
This essay addresses the connections of Research activity and LifeSkill development. It offers a review of the research experiences of PhD students in Education Sciences and Psychology at the University of Florence, emphasizing problems that affect people's lives from a translational perspective.